Empathising and Defining the Strategy Development Process Adoption of Industrial 4.0 in SMEs - Kurniawanti; Subagyo; Muhammad Kusumawan Herliansyah; Andi Sudiarso (School of Industrial and System Engineering, Telkom University, 2023)
The advent of Industry 4.0 has become an integral part of the manufacturing industry, playing a crucialrole in boosting competitiveness and enhancing productivity within companies. Small and MediumEnterprises (SMEs), which contribute significantly to the national economy, must inevitably embracethe adoption of Industry 4.0 technology. However, the implementation of this technology at the SMEfaces numerous obstacles. To address these challenges and facilitate the transformation to Industry4.0 in SMEs, this research aims to construct a comprehensive adoption strategy. Currently in itspreliminary stage, the strategy development process primarily involves identifying stakeholders, theirneeds, and the goals they aim to achieve. Design thinking, specifically the empathize and define phase,is employed as the methodological approach. The information utilized in this study originates fromsystematic literature reviews conducted using PRISMA. The analysis of the gathered data hasidentified several stakeholders, including government entities, IT experts, management personnel, andemployees. However, for the purpose of creating user personas, the focus is narrowed down tomanagement and employees. User personas are instrumental in understanding the goals and potentialobstacles faced by these individuals. The culmination of this stage is the formulation of a problemstatement, which will be further refined in subsequent phases of the design thinking process.